The impact of vitamin D on clinical parameters and bone turnover biomarkers in ligature-induced periodontitis: An experimental study in rats - Muhammad Hilmi Zainal; Faizal Hafez Hidayat; Fouad H. Al Bayaty (Elsevier, 2023)
Objectives and Background: Vitamin D has been associated with an increased risk of tooth loss and the severity of periodontal diseases. This study aimed to evaluate the effect of vitamin D on the clinical, radiographic, and serum level changes of bone turnover biomarkers in ligature-induced periodontitis. Methods: A total of 28 rats were included in this study and divided into test groups: Vitamin D supplement (VS), Vitamin D deficient (VD), and control (CG). Ligature-induced periodontal tissue destruction was performed and kept for 21 days. Clinical attachment and radiographic changes were recorded, and serum samples were tested for Osteoprotegerin (OPG), Dickkopf-1 (DKK1), Sclerostin (SOST), and Fibroblast growth factor 23 (FGF23) on the initial and final day of the study. Results: Groups that were made VD exhibited a more significant amount of clinical attachment loss (1.05 ± 0.50 mm) compared to the CG (0.83 ± 0.14 mm) and VS group (0.60 ± 0.13 mm), showing significant differences (p < 0.05). The radiographic alveolar bone loss amount was greater in the VD group compared to the other groups. For serum level assessment, the VD groups also exhibited a statistically significant reduction in the levels of OPG. They showed higher concentrations of DKK1, SOST, and FGF23 than other groups, with significant differences (p < 0.05). Conclusion: The results revealed that Vitamin D may play a role in the progression of periodontal disease. It was found to affect both clinical parameters and bone turnover biomarkers, suggesting its potential impact on the disease process.